La gouvernance locale, une forme de développement local et durable? Une illustration par les pays - Damien Talbot (Développement Durable et Territoires)
Can the local governance have characteristics of sustainability ? After having reconsidered the ambiguous function of the geographical proximity, this article defines the local governance, understood like an association of geographical, institutional and organisational proximities. Moreover, this paper looks into the question of sustainable character of local governance. An illustration by the “pays” comes to support the analysis and shows that sustainable principles of interdependence and ethics are partially applied. However, this sustainable character is limited.